The Role of Artificial Intelligence in the Influence of Auditor Abilities on Audit Quality - Fadli, Muhammad; Marietza, Fenny (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Purpose: This study aims to investigate the influence of auditor abilities on audit quality, with artificial intelligence (AI) as a moderating variable, addressing inconsistencies in prior research and exploring the potential role of AI in enhancing this relationship. Method: A quantitative approach was employed, utilizing questionnaires to collect data from 43 external and government auditors in Bengkulu City. The data were analyzed using Structural Equation Modeling Partial Least Square (SEM-PLS) to examine the relationships between variables. Results: The findings reveal that auditor abilities have a significant and positive impact on audit quality. However, the moderating effect of AI on this relationship was found to be insignificant, indicating limited integration of AI in current auditing practices in the region. Implications: The study underscores the importance of developing auditor skills and leveraging AI to potentially enhance audit quality in the future. It highlights the need for further technological adoption in auditing practices to fully realize AI's potential benefits. Novelty: This research contributes to the literature by integrating AI into the discourse on auditor competence and audit quality, offering a fresh perspective on the interplay between human skills and technological advancements in the auditing domain.